SERUM ENZYME ACTIVITIES AND ELECTROLYTE CONCENTRATIONS OF BREEDING DONKEYS (Equus asinus): EFFECT OF SEX, AGE, LACTATION AND/OR PREGNANCY - A. S. Qureshi; M. Ali (Journal of Animal and Plant Sciences, 2016)
Influence of sex, age in males and lactation and/or pregnancy in females on serum activities of four enzymes and concentrations of six electrolytes in 62 apparently healthy breeding donkeys comprising of 33 males and 29 females were studied. Statistical analysis revealed that out of 10 parameters: a) Sex affected activities of four enzymes namely, ALT, AST, LDH and y-GT significantly: Females showed significantly higher values of these enzymes; b) Age in males altered only two enzymes namely LDH and y-GT while electrolytes remained unaltered. Young foals aged less than 1 year showed highest values among these parameters whereas 3-7 year and above 10 year old donkeys showed the lowest values of LDH and y-GT, respectively; c) Lactation and/or pregnancy in females affected activities of 4 enzymes ALT, ALP, LDH and y-GT and concentrations of two electrolytes i.e., K and Cl. Non-pregnant dry animals showed significantly (P<0.05) lower activities of four serum enzymes i.e., ALT, ALP, LDH and y-GT than the rest of all physiological states of females under study except AST which remained unaltered.  It is concluded that physiological states, performed by corresponding hormones, leading to mild or transitional stresses play the all important regulatory role which has substantial function in the maintenance of stable homeostasis.
Keywords: Donkey; serum; enzymes; electrolytes; sex; age; lactation; pregnancy